Effect of Amylose Content on the Formation and Physicochemical Properties of Starch-Fatty Acid Complex - Chenggang HUANG; Jinyuan LI; Renyuan XU; Na LIU; Shaopeng YU; Ju LIU; Dongwei GUO (Shipin gongye ke-ji, 2022)
In this study, three different starch-lipid complexes were prepared using corn starch and stearic acid with different straight branch ratios as raw materials. Then the external morphology, crystal structure, digestibility, sustained release and other characteristics of the starch-lipid complex were determined by scanning electron microscopy, X-ray diffraction and fourier transform infrared spectroscopy. The results showed that: Compared with the original starch, the volume of the compound was increased, and the surface was uneven by scanning electron microscope. Infrared spectroscopy proved the formation of starch-lipid complexes, and the increase in hydrogen bonds might lead to an increase in resistant starch content. The complexs generated a diffraction angle of the V-type crystal structure. After treatment, normal corn starch (normal) and high amylose corn starch (G60) reduced the content of rapidly digestible starch (RDS), increased the content of slowly digestible starch (SDS), and increased the content of resistant starch (RS). The content of resistant starch reached to 52.0% and 52.4%. The release of stearic acid in the compound was divided into two stages, showing a trend of fast first and then slow, and the increase of amylose content could significantly improve the sustained release ability of the compound for stearic acid. This article could provide a reference for further improving the application scope of amylose.